THE FUTURE OF EDUCATIONAL LEADERSHIP IN INDONESIA IN THE 21ST CENTURY: LITERATURE STUDY - Agustin Hanivia Cindy; Poltjes Pattipeilohy; Johan Pattiasiasina; Nur Rina Priyani Mirsa; Alpendi; Muhammad Faizal A. Ghani (Program Studi Manajemen Pendidikan, 2025)
This article aims to analyze the trends, challenges, and necessary directions for educational leadership in Indonesia in facing the demands of the 21st Century, which are inclusive, innovative, and globally competitive. The research method used is a Systematic Literature Review (SLR) which involves the synthesis of literature from various scientific databases. The review results indicate that global transformation, especially the implementation of the Merdeka Curriculum (Independent Curriculum), positions the School Principal as the central driver of change, who is required to integrate technology with humanistic values and local context. Specifically, this review identifies that a hybrid leadership style that combines Digital Leadership and Transformational Leadership is the most crucial and needed style for fostering a culture of innovation and technological readiness in schools. This hybrid style is effective in activating coaching mechanisms that empower teachers. However, the findings also highlight a significant literature gap, particularly concerning effective and contextual Educational Leadership strategies in the 3T regions (Frontier, Outermost, Underdeveloped) and in Islamic educational institutions (Madrasahs), where infrastructure challenges and curriculum dualism require a different leadership model. The conclusion of this study confirms that future educational leadership must transcend administrative tasks and focus on a transformative function. Strengthening hybrid leadership that is responsive to Indonesia's diverse context is a critical investment to achieve the vision of Indonesia Emas 2045 (Golden Indonesia 2045).